2020
DOI: 10.1186/s42269-020-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Response and productivity of Garlic (Allium Sativum L.) by different levels of potassium fertilizer in farm soils

Abstract: Background: Garlic (Allium sativum L.) has been used as a medicine throughout ancient and modern history; it has been taken to prevent and treat a wide range of conditions and diseases. In Bangladesh, the demand for garlic increases day by day, but on the other hand, due to a shortage of land, production of garlic is not up to the mark. However, to solve the problem, a pot culture experiment was conducted at the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…In this study, more P in cloves was determined in cultivation with S (0.42% DM on average) without mineral fertilization than without S (0.38% DM on average). Jiku et al [73] determined the P content in garlic cloves at the level of 0.15% DM in cultivation without K fertilization (K0) and 0.35% in cultivation with K 200 kg ha −1 . The above-cited authors also showed that potassium increases the N content in garlic bulbs.…”
Section: Macro-and Micronutrients Enrichment and Their Contentmentioning
confidence: 99%
“…In this study, more P in cloves was determined in cultivation with S (0.42% DM on average) without mineral fertilization than without S (0.38% DM on average). Jiku et al [73] determined the P content in garlic cloves at the level of 0.15% DM in cultivation without K fertilization (K0) and 0.35% in cultivation with K 200 kg ha −1 . The above-cited authors also showed that potassium increases the N content in garlic bulbs.…”
Section: Macro-and Micronutrients Enrichment and Their Contentmentioning
confidence: 99%
“…Scientists reported that the uptake of different nutrients by garlic plant varied significantly due to the different application levels of K. Potassium alone induced maximum uptake of all the elements studied (N, P, K, S, Ca, Mg, B, and Na) at K at 200 kg•ha −1 and the lowest in control K0 treatment [29]. It was found that these essential and beneficial nutrients could protect crop plants against both abiotic and biotic stresses by enhancing the plant resistance power and regulating the mineral nutritional status [32].…”
Section: Nutritional and Chemical Composition Of Garlic Leavesmentioning
confidence: 99%
“…Proline accumulation is a common physiological response in many plants in response to a wide range of biotic and abiotic stresses [33]. It is obvious from data presented in Table 4 that Jiku et al [29] reported that the maximum total yield and size of garlic bulb were obtained with potassium application at 200 kg [31], K is responsible not only for higher production but also for the improved quality of the harvest. Thus, K…”
Section: Nutritional and Chemical Composition Of Garlic Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, contents of N, P and K in leaf and bulbs of garlic and volatile oils in bulbs were much increased by increasing N-level (Naruka, 2002 andShokr, 2005). Likewise, several researchers reported that garlic plants growth and yield were improved by application of potassium (El Sayed and El Morsy, 2012;Arisha et al, 2017 andJiku et al, 2020). Furthermore, Maupua and Rathoipe (2007), Shiferaw et al (2015) and Khan et al (2016) found that the garlic plant growth, yield and its quality were increased with increasing NP and/or NK rates.…”
Section: Introductionmentioning
confidence: 97%